Research and characterization of selected pathogens of cutaneous and mucocutaneous lesions in cetaceans from the Brazilian coast - Yagüe, Carlos Sacristán (2017)
Cetaceans are sentinels of the marine environment, currently threatened by many factors, mainly anthropogenic. The most easily identified compromising conditions are those affecting the skin and external mucosae - good indicators of the cetaceans health status. Cutaneous and mucocutaneous lesions have been extensively reported in wild and captive cetaceans, but little is known about the involved etiological factors, evolution of the dermatological lesions and their systemic consequences. Viruses are the most commonly involved agents in cutaneous and mucocutaneous lesions, especially herpesviruses (HV) and, associated with skin and mucosal lesions with varying morphologies, and cetacean poxviruses (CePV), mainly associated with characteristic tattoo or ring skin lesions. In addition, fungal agents are also recognized as causative agents of dermatological disease in cetaceans, especially in the process known as paracoccidioidomycosis ceti, observed as raised proliferative whitish lesions, caused by non cultivable yeast of Paracoccidioides brasiliensis (order Onygenales). Despite being reported worldwide, the occurrence of these etiological agents in southern Atlantic cetaceans is still poorly understood. The goal of this study was to identify and characterize selected cutaneous and mucocutaneous pathogens (HV, CePV and P. brasiliensis) of free-ranging cetaceans from Brazil, and to design more sensitive diagnostic methods for their detection. All the studied cetaceans stranded along the coast of Brazil, between 2005 and 2015, except three wild riverine dolphins that were physically contained and released after sample collection. In order to achieve our goals, we employed molecular, histopathological, and occasionally immunohistochemical and electron microscopy techniques. The presence of HV and CePV was evaluated in cutaneous, and oral and genital mucosal samples from 115 specimens and skin samples from 113 individuals, respectively; whereas the presence of members of the genus Onygenales sp. was evaluated in four specimens presenting macroscopic compatible lesions. Skin or oral mucosal samples from four animals were HV PCR-positive: a whitish ulcerated skin lesion from a Guiana dolphin (Sotalia guianensis), a lingual sample from an Atlantic spotted dolphin (Stenella frontalis), ulcerative lesions and healthy skin samples from a dwarf sperm whale (Kogia sima), and a proliferative skin lesion from a Bolivian river dolphin (Inia boliviensis). The tree first animals were infected with alphaherpesvirus. A sequence more similar to gammaherpesvirus was obtained from the Bolivian river dolphins proliferative skin lesion. The Bolivian river dolphin sequence could possibly be a member of a new gammaherpesvirus genus. Additionally, all other available tissue samples from HV-positive specimens, aside from skin and oral mucosa, were also tested by PCR and histologically evaluated. A different alphaherpesvirus sequence was found in the stomach and in a mesenteric lymph node of the dwarf sperm whale. Microscopic findings in two HV-positive animals (chronic proliferative dermatitis in Bolivian river dolphin and Guiana dolphin) were compatible with HV. CePV was identified in tattoo skin lesions of an Atlantic bottlenose dolphin and a Guiana dolphin by established molecular methods, and poxviral particles were observed by electron microscopy. CePV-positive animals presented epidermal ballooning degeneration and occasionally small, pale eosinophilic or amphophilic intracytoplasmic inclusions, compatible with CePV. Specific amino acid motifs for all CePV were also identified, reinforcing the suggestion of the new Cetaceanpoxvirus genus. We also designed novel SYBR® Green real-time and conventional CePV PCR methods significantly more sensitive than those currently available in the literature. An additional Guiana dolphin, previously negative based in established PCR methods was diagnosed positive for CePV through these new techniques. Refractile yeasts (49 µm in diameter) were observed under light microscopy in mild granulomatous and necrotic skin lesions of four Atlantic bottlenose dolphin, and for the first time, in a skeletal muscle abscess (the former possibly indicating the invasive potential of the agent). Onygenales sp. yeasts were identified in skin lesions by immunohistochemistry and a sequence of P. brasiliensis, more similar (100% nucleotide identity) to the one described in an Atlantic bottlenose dolphin from Cuba than to human or any other terrestrial mammals cases in Brazil, was obtained from the skin lesion of one of the specimens, confirming the etiological agent of these type of lesions. Herein we report the first molecular identification of HV in South American cetaceans and in riverine dolphins worldwide. This study also describes the first amplification of CePV and P. brasiliensis in odontocetes from South America. Four of the five novel herpesvirus sequences herein identified are possibly novel species, tentatively named Delphinid HV-10, Kogiid HV-2, Kogiid HV-3 and Iniid HV-1.